Self-compassion modulates autonomic and psychological responses to stress among adults with generalized anxiety disorders - Lijun Sun; Xuejun Qi; Xi Luo; Ying Wang; Xianwei Che; Yonghui Shen (Frontiers in Psychiatry)
BackgroundSelf-compassion is associated with emotional well-being, yet its benefits in generalized anxiety disorder (GAD) patients remain unclear. This study investigated the impact of self-compassion on emotional and physiological stress responses in individuals diagnosed with GAD.MethodsSeventy-seven GAD patients were categorized into high (n = 39) and low (n = 38) self-compassion groups using the Self-Compassion Scale. Electrocardiograms were recorded during a stress-inducing task, in which negative feedback was provided on personal intelligence and career development. Participants reported state anxiety and perceived stress pre- and post-task.ResultsWhen exposed to a stressor, individuals with higher self-compassion had lower heart rates (t(75) = -2.06, p = 0.043), higher heart rate variability (t(75) = 2.73, p = 0.04), and lower anxiety (t(75) = -2.07, p = 0.041) compared to the lower self-compassion group. Moreover, heart rate variability was negatively correlated with anxiety across patients (r = -0.31, df = 75, p = 0.03).ConclusionThese results highlight the role of self-compassion in managing psychological and physiological responses to stress in GAD patients and indicate the potential of self-compassion interventions in GAD treatments.